Privacy Technologies and Policy First Annual Privacy Forum, APF 2012, Limassol, Cyprus, October 10-11, 2012, Revised Selected Papers - Preneel, Bart; Ikonomou, Demosthenes (Security and Cryptology, 2014)
This book constitutes revised selected papers from the First Annual Privacy Forum, APF 2012, held in Limassol, Cyprus, in October 2012. The 13 revised papers presented in this volume were carefully reviewed and selected from 26 submissions. They are organized in topical sections named: modelling; privacy by design; identity management and case studies.